2018
DOI: 10.1002/ccd.28001
|View full text |Cite|
|
Sign up to set email alerts
|

Reducing radiation dose: Equipment, procedure, and operator Perfecting the Trifecta

Abstract: This article illustrates the positive impact of fluoroscopic imaging equipment on radiation dose reduction in CTO PCI.• The reader should recognize the importance of purchasing and maintaining the best equipment, understanding procedure/patient complexity, and assuring operator training in radiation dose reduction.• Future efforts/studies should focus upon all three areas of dose reduction for best results.Radiation safety in the cardiac catheterization laboratory has been an important aspect of patient care f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 4 publications
(4 reference statements)
0
2
0
Order By: Relevance
“…Many publications focus on radiation protection issues in fluoroscopy and specially in interventional procedures [1,[57][58][59][60][61][62][63][64][65][66]. The common feature of all studies is that patient dose optimization in interventional procedures occurs by a combination of equipment protocol modification and operator behaviour, and not simply by changing the protocol characteristics.…”
Section: Fluoroscopymentioning
confidence: 99%
See 1 more Smart Citation
“…Many publications focus on radiation protection issues in fluoroscopy and specially in interventional procedures [1,[57][58][59][60][61][62][63][64][65][66]. The common feature of all studies is that patient dose optimization in interventional procedures occurs by a combination of equipment protocol modification and operator behaviour, and not simply by changing the protocol characteristics.…”
Section: Fluoroscopymentioning
confidence: 99%
“…The active use of digital processing, customization of exam protocols, removal of antiscatter grid in specific clinical cases (such as spinal digital subtraction angiography), reduction of pulse rate and frame rate, default use of the fluoroscopy mode at low level, as well as continuous dose monitoring and patient follow-up, are suggested. The new technology features that currently accompany state-of-the art X-ray angiography machines provide potential for dose optimization but their use and their effect on radiation dose must be clearly understood [62,63]. A recent study by Tsalafoutas et al has shown that protocol setting has a large impact on image characteristics and radiation exposure, and that these protocols do not always perform as expected [23].…”
Section: Fluoroscopymentioning
confidence: 99%